A hyaluronic acid-binding contact lens with enhanced water retention. Issue 2 (April 2015) - Singh, Anirudha; Li, Peter; Beachley, Vince; McDonnell, Peter; Elisseeff, Jennifer H.
Abstract Purpose As a main component of an artificial tear or eyedrop, hyaluronic acid (HA) prolongs water retention, slows tear removal, improves tear film stability, reduces protein adsorption at the ocular surface and permits uninterrupted blinking. Here, we hypothesized that the contact lens modified with an HA-binding peptide (HABpep) could locally bind and concentrate exogenous HA present in eyedrops to the modified contact lens surface, which exhibited superior water retention. Methods To bind HA, a contact lens surface was covalently modified by HABpep with and without a poly(ethylene glycol) (PEG) spacer. Bound HA and its retention over time on the modified surfaces were evaluated by fluorescence measurements. A comparative water evaporation study was performed to determine water retention in an HA-bound contact lens. Results Fluorescence studies showed that the contact lens was successfully modified by HABpep with or without a PEG spacer, and HA bound to the contact lens surface. Furthermore, the bound HA via HABpep significantly reduced water loss from the modified contact lens. Conclusion HABpep strategies that locally bind and concentrate HA to create a thin coating of a therapeutic molecule on surfaces could provide physical and biological benefits to treat ocular surface dysfunction. The surface bound HA via HABpep enhanced water retention in the modified contact lens.